Effect of thermochemical activation temperature on electrical conductivity and concentration of charge carriers in the obtained porous carbon materials - Rachiy, B.I.; Ivanichok, N.Ya.; Moklyak, V.V.; Kolkovskyi, P.I.; Bulbuk, O.I.; Soltys, A.M.; Borchuk, D.S.; Khrushch, L.Z. (Physics and Chemistry of Solid State, 2024)
By changing the temperature of chemical activation of plant biomass, nanoporous carbon materials with a specific surface area of up to 1050 m2/g were obtained. The obtained carbon materials were used to form composites with different percentages of conductive additive. Electrochemical impedance spectroscopy was used to investigate the physicochemical processes occurring at the carbon electrode/electrolyte interface in a 30% aqueous KOH solution. The concentration of charge carriers in the obtained carbon materials was determined, the values of which are in the range of 6·1018 – 35·1018 cm-3, and its dependence on the temperature of thermochemical activation was established. It was established that an increase in the temperature of thermochemical activation from 600 ºС to 900 ºС leads to an increase in the capacity of the space charge region by almost 10 times. The formation of nanoporous carbon material/conductive additive composites contributes to the correlation between the values ​​of specific capacitance and electrical resistance for the studied materials.